Impact of Partial Oil Removal on Energy Content of Distillers Grains Plus Solubles for Finishing Cattle - Jordan E. Burhoop; Jessica L. Sperber; Curt J. Bittner; F. Henry Hilscher; Jim C. MacDonald; Galen E. Erickson (Animals, 2024)
Two experiments evaluated the impact of the reduction in the percentage of corn oil remaining in distillers grains plus solubles (DGS) after the ethanol plant de-oiling process or by adding corn oil back to DGS following de-oiling on finishing cattle performance and nutrient digestion. Experiment 1 utilized 320 yearling steers (initial BW = 413 kg; SD = 25 kg) fed in 32 pens (10 steers/pen) and assigned to one of four treatments (n = 8 pens/treatment). The four treatments consisted of a blended DRC:HMC corn control diet (CON), de-oiled modified distillers grains plus solubles included at 40% of diet DM (DODGS), de-oiled modified distillers grains plus solubles included at 38% of diet DM plus 2% added corn oil (DODGS + Oil), and full-fat modified distillers grains plus solubles included at 40% of diet DM (FFDGS). The DODGS product contained 8.9% fat while the FFDGS product contained 11.6% fat. Dry matter intake (DMI) was impacted by treatment (p = 0.01) with steers fed DODGS having the greatest DMI and steers fed CON, DODGS + Oil, and FFDGS having lower DMI. Dietary treatment tended to impact ADG (p = 0.06) with steers fed DODGS and DODGS + Oil having greater gains than CON, with FFDGS being an intermediate. As a result of increased ADG, G:F differed between treatments (p < 0.01) with the greatest feed efficiency observed for steers fed DODGS + Oil and FFDGS. Including MDGS in the diet improved G:F by 6 to 11% compared to feeding DRC:HMC corn blend, with an improvement in G:F of 4.9 and 1.2% for DODGS + Oil and FFDGS, respectively, compared to DODGS. Hot carcass weight was impacted by dietary treatment (HCW; p = 0.05), with DODGS- and DODGS + Oil-fed steers having the heaviest HCW, CON steers having the lightest HCW, and FFDGS being an intermediate. Experiment 2 was a 5 × 4 unbalanced Latin rectangle digestion experiment with four diets, five ruminally cannulated steers, and five periods that utilized the same treatments as Exp. 1. Dietary fat measured 4.2, 6.0, 7.9, and 7.1% for CON, DODGS, DODGS + Oil, and FFDGS, respectively. Intakes of DM, OM, and energy as well as total tract fat digestibility and DE (Mcal/d) were not impacted by dietary treatment (p ≥ 0.46). When corn oil was added back to de-oiled MDGS, there was a negative impact on digestibility of OM (p < 0.01) and NDF (p = 0.07) compared with DODGS, FFDGS, and CON. Partially removing oil from modified distillers grains plus solubles did not significantly impact cattle performance, carcass traits, energy content, or digestibility when MDGS was included at approximately 40% of diet DM.